Anterior insula and inferior frontal gyrus: where ventral and dorsal visual attention systems meet. Issue 1 (26th December 2020) - Cazzoli, Dario; Kaufmann, Brigitte C; Paladini, Rebecca E; Müri, René M; Nef, Tobias; Nyffeler, Thomas
Abstract: The clinical link between spatial and non-spatial attentional aspects in patients with hemispatial neglect is well known; in particular, an increase in alerting can transitorily help to allocate attention towards the contralesional side. In models of attention, this phenomenon is postulated to rely on an interaction between ventral and dorsal cortical networks, subtending non-spatial and spatial attentional aspects, respectively. However, the exact neural underpinnings of the interaction between these two networks are still poorly understood. In the present study, we included 80 right-hemispheric patients with subacute stroke (50% women; age range: 24–96), 33 with and 47 without neglect, as assessed by paper–pencil cancellation tests. The patients performed a computerized task in which they were asked to respond as quickly as possible by button-press to central targets, which were either preceded or not preceded by non-spatial, auditory warning tones. Reaction times in the two different conditions were measured. In neglect patients, a warning tone, enhancing activity within the ventral attentional 'alerting' network, could boost the reaction (in terms of shorter reaction times) of the dorsal attentional network to a visual stimulus up to the level of patients without neglect. Critically, using voxel-based lesion-symptom mapping analyses, we show that this effect significantly depends on the integrity of the right anterior insula and adjacent inferior frontal gyrus, i.e., right-hemispheric patients with lesions involving these areas were significantly less likely to show shorter reaction times when a warning tone was presented prior to visual target appearance. We propose that the right anterior insula and inferior frontal gyrus are a critical hub through which the ventral attentional network can 'alert' and increase the efficiency of the activity of the dorsal attentional network. Abstract : In right-hemispheric patients with neglect, the ability to benefit from non-spatial warning tones to shorten reaction times to visual stimuli depends on the integrity of the anterior insula and inferior frontal gyrus. Cazzoli et al. propose these regions as a hub through which the ventral attentional network 'alerts' its dorsal counterpart. Graphical Abstract: